Desenvolvimento de reação em cadeia da polimerase e ecoepidemiologia de Conidiobolus lamprauges em ovinos de Alto Paraguai, Mato Grosso - Silveira, Marcelo Marques da (2012)
The conidiobolomycosis is a granulomatous disease associated by the fungus Conidiobolus spp. observed in humans and animals. The traditional techniques for the diagnosis of the disease are isolation of the agent associated with epidemiological aspects and the presence of typical clinical signs and pathological conditions. This work describe the development of Conidiobolus lamprauges specific PCR in order to detect the presence of fungus in clinical samples. Samples of tissue suspected of animals were collected and sent to fungal culture, histopathologic testing and PCR amplification. PCR reactions were performed using DNA extracted from fresh and paraffin embedded tissues with universal primers for fungi and amplifying fragment of the 18S region. rDNA region and specific primers were designed based on the same gene for C. lamprauges, which generated products with approximately 540 bp and 222 bp, respectively. The culture was positive in 26.6% of clinical samples. PCR tests for C. lamprauges showed DNA amplification in fresh tissue (80%) and paraffin (44.4%). Environmental samples were also collected in a property where there was an outbreak of disease, in order to carry out the study to detect possible sources of infection for sheep. During twelve months, plant and water samples were collected, their DNA extracted and analysed by to qPCR. In the analysis of environmental samples, six were positive for C. lamprauges in plant and three in water samples. The standard curve was generated resulting in a detection limit of 1 fg of DNA from C. lamprauges (3.4 x 102 molecules), ε = 0.98, R2= 0.98 and slope = -3.3. The results showed that there was no relationship between the presence of the fungus in plant material with the rainy season observed in the study. In conclusion, the PCR technique described here shows a high sensitivity and specificity for detection of C. lamprauges in clinical samples of fresh and paraffin, becoming a tool to a rapid, and the seasonality disease may not be closely related to the presence of the agent in the environment, for C. lamprauges was observed in different seasons, but were quantified at different levels during the period of study.